Mildi-LIS®, an online decision support system for treatment against potato late blight - Gaucher, Denis (MTT, 2007)
Mildi-LIS® is an online decision support system that allows a reduction of the number of treatments against late blight potato. It is based on the epidemiological model Premil from ARVALIS Institut du végétal researches. The institute works since 1998 to adapt the Ullrich Schrödter model to french climatic conditions. Premil is validated since 2002. In the years 2002 and 2003, Arvalis sold a PC-version but the potato growers asked Arvalis to develop an internet version. An online system is better to exchange data between technicians and growers.
Keywords: Ka; potato; late blight; DSS; epidemiological model